Poema Lo somni (1831). - MARTÍ-BADIA, ADRIÀ (Scripta)
The article reviews the Poem Lo somni (1831) by Vicent Salvà, highlighting the complete edition carried out by Germán Ramírez Aledón. The importance of the poem in the early stages of the Valencian Renaixença is emphasized, and linguistic and formal aspects of the poem are detailed. The private edition consists of 150 numbered copies, and the reproduction of the original poem for the first time in history is highlighted. Ramírez Aledón is encouraged to complete the publication of Salvà's correspondence for future research.